Feasibility, Engagement and Effectiveness of Digital Health Interventions for Postpartum Weight Management: A Systematic Review - Siti Zuhaidah Shahadan; Nurul Mutmainnah Yusof; Mohamad Firdaus Mohamad Ismail (INTERNATIONAL JOURNAL OF CARE SCHOLARS, 2026)
Background: Postpartum weight retention contributes to long-term obesity and cardiometabolic risk. Digital health interventions have emerged as potential weight-management strategies. This review characterise digital postpartum weight-management interventions and synthesise evidence on feasibility, acceptability, engagement, user perceptions, weight-related outcomes, and cardiometabolic outcomes among postpartum women with overweight or obesity. Methods: A systematic search was conducted in Scopus to identify articles evaluating digital or technology-supported interventions for postpartum weight management. Included articles involved postpartum women with overweight or obesity and reported outcomes related to feasibility, acceptability, engagement, user perceptions, weight-related outcomes, or cardiometabolic indicators. Methodological quality was appraised using design-appropriate Joanna Briggs Institute tools. Due to heterogeneity in study design and outcomes, the findings were synthesized narratively. Results: Seven articles were included: randomised and feasibility trials, a retrospective cohort study, and a qualitative study. Interventions included mobile applications, wearable-supported programmes, social media groups, telephone support, and blended-care approaches. Acceptability was generally favourable, whereas engagement varied across studies and intervention components. Weight-related findings were mixed, with some studies reporting favourable changes and others minimal or non-significant between-group differences. No study reported biochemical cardiometabolic outcomes. One feasibility trial reported blood pressure and waist circumference. Conclusion: Digital health interventions may be feasible and acceptable approaches to postpartum weight management, but their effectiveness remains uncertain due to a small, heterogeneous, and methodologically limited evidence base.